2001
DOI: 10.2307/3061098
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation for Pasture Alters Nitrogen and Phosphorus in Small Amazonian Streams

Abstract: The clearing of moist, lowland tropical forest for cattle pasture represents a widespread land use change that has consequences for soil biogeochemical cycles, as well as the links between soil processes and the concentrations of dissolved and particulate materials in rivers and streams. We examined how conversion of tropical forest to actively grazed cattle pasture in the Brazilian Amazon influenced the concentrations of different forms of nitrogen (N) and phosphorus (P) in soil solution and stream water. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
1
17

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 38 publications
(56 reference statements)
10
97
1
17
Order By: Relevance
“…Changes to riparian plant communities can potentially alter the quality and availability of basal leaf litter resources in tropical stream food webs. These Wndings are important given that lowland tropical riparian forests are becoming severely degraded, often suVering decreases in tree species diversity and abundance (Pringle et al 2000;Neill et al 2001;Benstead et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Changes to riparian plant communities can potentially alter the quality and availability of basal leaf litter resources in tropical stream food webs. These Wndings are important given that lowland tropical riparian forests are becoming severely degraded, often suVering decreases in tree species diversity and abundance (Pringle et al 2000;Neill et al 2001;Benstead et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, decreased N retention in streams could be due partially to a net decrease in C:N of the nutrient pools left behind (after export), concomitant increases in N-specific uptake rates in biomass and, ultimately, saturation of biotic demand. Removal of tropical forest increased N limitation by decreasing N inputs from terrestrial vegetation and soils (Neill et al 2001), suggesting that removal of C-rich litter sources does not always decrease N limitation.…”
Section: C:n and N-specific Uptakementioning
confidence: 98%
“…Thus, the study of small catchments can integrate many processes in changing landscapes (Alexander et al 2000;Campbell et al 2004). For example, Neill et al (2001) working in the western Amazon demonstrated changes in solute concentrations with lower nitrate concentrations and decrease in N:P ratios in streams draining pastures relative to forests, in addition to higher concentrations of total suspended solids, particulate organic carbon and particulate organic nitrogen in the dry season. The observed decrease in stream NO 3 -in pastures was consistent with previous studies that found lower extractable NO 3 -concentrations and lower rates of net N mineralization and net nitrification in the soils of the pasture watersheds compared with forest watersheds (Neill et al 1995).…”
Section: Introductionmentioning
confidence: 97%
“…While studies evaluating the effects of changes in land use and land cover on the biogeochemistry of rivers in Brazil are relatively common in the Amazon Neill et al 2001;Ballester et al 2003;Biggs et al 2002Biggs et al , 2004Figueiredo et al 2010), biogeochemical evaluations of the impacts of land use changes in the Cerrado region are still scarce in spite of its hydrological importance on a country-wide scale. Some of the most important hydrological basins in Brazil have their headwaters in the Cerrado: Araguaia-Tocantins, Paraná, and São Francisco basins.…”
Section: Introductionmentioning
confidence: 98%